Effects of Ethanol Extract of Rosa damascene on HbA1c Level and NF-κB Expression in Diabetic Rats - Choirotussanijjah Choirotussanijjah; Harianto Notopuro; Ema Qurnianingsih (Universitas Nahdlatul Ulama Surabaya, 2021)
Diabetes mellitus (DM) is a chronic hyperglycemic that can cause complications in several organs. It could lead glycosylated hemoglobin or HbA1c formation which has ability undergo further changes into Advanced Glycation End Products (AGEs) and stimulate activation of transcription factors such as nuclear factor kappa B (NF-κB). Some studies showed that anthocyanin has antioxidant and anti-inflammatory activity and it has been found Rosa damascene contain high level of anthocyanin. Total anthocyanin content was 0.459 ± 0.003 mg/L. The aim of this study was to investigate inhibitory effect of R. damascena extract on HbA1c levels and NF-κB activation in diabetic rats. Male wistar rats (n=24) were divided into 6 groups as normal control (KN), streptozotocin-induced diabetic control (KP), diabetic treated with R. damascene (P1, P2, P3; 250, 500 and 1000 mg/kg/d respectively) and diabetic treated with metformin (KM; 500 mg/kg/d). This was carried out for 28 days. The inhibition mode of R. damascene extract was examined by measuring HbA1c levels and expression of NFκB by immunohistochemistry. The results showed p values ​​> 0.05 for HbA1c and p < 0.05 for NFκB. From immunohistochemical staining, it seen the expression of NFκB was low in treated group (P1, P2, P3 and KM) compared with KP. Thus, oral administration of R. damascene extract for 28 days could not reduce HbA1c levels, but can supress NFκB expression.